Evaluation of the Trans Halim City Transportation Business Activity Policy, Puskopau Unit, Halim Perdana Kusuma Jakarta, in the Perspective of Public Policy and Law Number 5 of 1999 - Alfian Kusuma; Sri Kamariyah; Sri Roekminiati (International Journal of Social Welfare and Family Law, 2026)
This study aims to evaluate the public policy of Trans Halim city transportation business activities managed by the Air Force Cooperative Center (PUSKOPAU) at Halim Perdana Kusuma Airport, Jakarta, in the perspective of public policy theory and Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. Using empirical juridical research with a socio-legal approach combined with policy evaluation frameworks including the Dunn model and CIPP evaluation approach, this study examines the alignment between PUSKOPAU's territorial-based business operations and the regulatory mandates of Indonesian competition law. Field observations and interviews conducted with drivers, management, and transportation organization representatives confirm that PUSKOPAU operates as a sole provider on specific routes within and around the Halim Perdana Kusuma military complex, constituting indicators of natural monopoly behavior. The study applies rule of reason analysis and public interest theory to assess whether such monopolistic conditions are justified by cooperative law exemptions under Article 50(i) of Law No. 5/1999. Findings reveal that while PUSKOPAU's operations serve member welfare objectives consistent with cooperative law, the extension of services to the general public creates a legal grey area, particularly given the absence of KPPU regulatory guidelines for cooperative exemptions. This legal gap produces significant policy uncertainty and hampers effective enforcement. The article recommends that KPPU promptly formulate specific guidelines for cooperative monopoly exemptions and that formal KPPU investigation procedures be initiated to determine the legality of PUSKOPAU's market dominance.